ARRANGEMENTS FOR THE CUSTODY OF COMPENSATION FOR UNKNOWN PARTIES IN THE FRAMEWORK OF LAND ACQUISITION FOR DEVELOPMENT IN THE PUBLIC INTEREST - Syeh Aries Fauzan; Mohammad Hamidi Maskur; Herlindah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Although the general provisions for consignment of compensation have been regulated in land acquisition regulations, this study identified the incompleteness of explicit legal norms regarding the basis and procedures for consignment on the grounds that the entitled party is unknown. The focus of this study lies in whether the District Court is justified in granting a consignment application for public interest development on the grounds that the entitled party is unknown, reviewed from the concept of land ownership in Indonesia and comparative law with Malaysia. Through a normative legal approach and legal comparison, this study found that the court's decision to grant consignment for an unknown party is contrary to the basic concept of the State's Right to Control (HMN) as regulated in Article 33 paragraph (3) of the 1945 Constitution in conjunction with Article 2 of Law Number 5 of 1960. Legally, if there is no legal subject ownership right attached to the land, the status of the land essentially returns to State Land, so that efforts to consign compensation become irrelevant and normatively unnecessary. This finding emphasizes the importance of legal certainty in the implementation of land acquisition regulations.